Pemanfaatan Digital Marketing di Masa Pandemi Covid-19 pada Industri dan Usaha Obat Tradisional - Muhammad Hasyim Ashari (Al-Muraqabah: Journal of Management and Sharia Business, 2022)
The purpose of this study is to analyze the impact of using digital marketing by the traditional medicine industry during the Covid-19 pandemic compared to conditions before the Covid-19 pandemic. This research is a descriptive quantitative research with a case study approach. The data used is secondary data in the form of  sales reports (turnover) in the period 2014 to 2021 obtained from the traditional medicine industry in Malang, East Java. From this data, it is then processed and analyzed using tables and graphs to provide a descriptive picture related to the problems in the study as well as conducting normality tests, homogeneity tests, and different tests (independent sample T-test) using SPSS Ver.19 software to produce a conclusion. study. The results show that the traditional medicine industry can develop during the Covid-19 pandemic by utilizing digital marketing as a sales system as evidenced by an increase in average sales (turnover) during the Covid-19 pandemic by 173% compared to the period before the pandemic Covid-19.